2003
DOI: 10.1128/jvi.77.14.7804-7813.2003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Functional Analyses of Kunjin Virus Infectious cDNA Clones Demonstrate the Essential Roles for NS2A in Virus Assembly and for a Nonconservative Residue in NS3 in RNA Replication

Abstract: A number of full-length cDNA clones of Kunjin virus (KUN) were previously prepared; it was shown that two of them, pAKUN and FLSDX, differed in specific infectivities of corresponding in vitro transcribed RNAs by ϳ100,000-fold (A. A. Khromykh et al., J. Virol. 72:7270-7279, 1998). In this study, we analyzed a possible genetic determinant(s) of the observed differences in infectivity initially by sequencing the entire cDNAs of both clones and comparing them with the published sequence of the parental KUN strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
143
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(148 citation statements)
references
References 28 publications
(41 reference statements)
2
143
0
Order By: Relevance
“…It was reported that NS2A binds with high specificity to the 3' untranslated region (UTR) of viral genomic RNA and to other components of the replication complex (Mackenzie et al, 1998). In addition, NS2A is considered to play roles in modulating the host-antiviral interferon response (Liu et al, 2004;Liu et al, 2006;Liu et al, 2005;Munoz-Jordan et al, 2003) and assembly/ secretion processes of virus particles (Kummerer and Rice, 2002;Leung et al, 2008;Liu et al, 2003). Although the exact membrane topology of NS2A is yet to be determined, NS2A of OHFV has been predicted to span the membrane of the endoplasmic reticulum five times by several transmembrane domain prediction programs (TMHMM (Krogh et al, 2001), and TMpred (Hofmann and Stoffel, 1993)).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that NS2A binds with high specificity to the 3' untranslated region (UTR) of viral genomic RNA and to other components of the replication complex (Mackenzie et al, 1998). In addition, NS2A is considered to play roles in modulating the host-antiviral interferon response (Liu et al, 2004;Liu et al, 2006;Liu et al, 2005;Munoz-Jordan et al, 2003) and assembly/ secretion processes of virus particles (Kummerer and Rice, 2002;Leung et al, 2008;Liu et al, 2003). Although the exact membrane topology of NS2A is yet to be determined, NS2A of OHFV has been predicted to span the membrane of the endoplasmic reticulum five times by several transmembrane domain prediction programs (TMHMM (Krogh et al, 2001), and TMpred (Hofmann and Stoffel, 1993)).…”
Section: Discussionmentioning
confidence: 99%
“…Different approaches have thus been used to improve the stability of full-length flavivirus cDNA clones [3]. Introns have been inserted to interrupt genes encoding products that may be toxic in bacteria [8,36], and relatively permissive E.coli strains have been identified. Full-length flavivirus cDNA from NY99, B956 and Kunjin WNV strains have previously been cloned in plasmids amplified in the HB101 E.coli strain [3,8,26].…”
Section: Discussionmentioning
confidence: 99%
“…Introns have been inserted to interrupt genes encoding products that may be toxic in bacteria [8,36], and relatively permissive E.coli strains have been identified. Full-length flavivirus cDNA from NY99, B956 and Kunjin WNV strains have previously been cloned in plasmids amplified in the HB101 E.coli strain [3,8,26]. In the present study, we employed a plasmid cloning strategy to construct an infectious clone of the IS-98-ST1 WNV strain (WNV-IC).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations